Clinical profiling of patients admitted with acute heart failure: a comprehensive survival analysis - López-Vilella, Raquel; Guerrero Cervera, Borja; Donoso Trenado, Víctor; Martínez Dolz, Luis; Almenar Bonet, Luis (Frontiers in Cardiovascular Medicine, 2024)
Background: In heart failure (HF), not all episodes of decompensation are alike. The study aimed to characterize the clinical groups of decompensation and perform a survival analysis. Methods: A retrospective study was conducted on patients consecutively admitted for HF from 2018 to 2023. Patients who died during admission were excluded (final number 1668). Four clinical types of HF were defined: low cardiac output (n:83), pulmonary congestion (n:1044), mixed congestion (n:353), and systemic congestion (n:188). Results: The low output group showed a higher prevalence of reduced left ventricular ejection fraction (93%) and increased biventricular diameters (p<0.01). The systemic congestion group exhibited a greater presence of tricuspid regurgitation with dilatation and right ventricular dysfunction (p:0.0001), worse renal function, and higher uric acid and CA125 levels (p:0.0001). Diuretics were more commonly used in the mixed and, especially, systemic congestion groups (p:0.0001). The probability of overall survival at 5 years was 49%, with higher survival in pulmonary congestion and lower in systemic congestion (p:0.002). Differences were also found in survival at 1 month and 1 year (p:0.0001). Conclusions: Mortality in acute HF is high. Four phenotypic profiles of decompensation differ clinically, with distinct characteristics and varying prognosis in the short, medium, and long term.